Pemberdayaan Kader Kesehatan melalui Pelatihan Terapi Komplementer Pijat Bayi untuk Meningkatkan Pengetahuan dan Keterampilan Kader di Kecamatan Tellu Siattinge Kabupaten Bone - Asrianti Safitri Muchtar; Ita Novianti; Desi Heriyana (Universitas Muhammadiyah Manado, 2026)
Infancy is a critical period of growth and development that requires appropriate stimulation, including complementary infant massage therapy. However, community health cadres often have limited knowledge regarding proper infant massage techniques, reducing the effectiveness of health education delivered to parents. This community service program aimed to improve the knowledge and practical skills of community health cadres regarding complementary infant massage therapy in Tellu Siattinge District, Bone Regency. The program involved fifteen health cadres from Otting Village, Lanca Village, Ulo Village, and Palongki Village. Activities included health education, demonstrations using infant mannequins, supervised practice, and evaluation through pretest and posttest assessments. The findings indicated a substantial improvement in participants' knowledge following the intervention. Before the training, most participants demonstrated moderate knowledge (66.67%), whereas after the intervention, 80.00% achieved good knowledge, and no participant remained in the poor knowledge category. Participants also demonstrated appropriate infant massage techniques during practical evaluations. These findings indicate that practice-based cadre empowerment effectively improves cadres' competence in educating parents regarding infant massage. Sustainable training programs are recommended to strengthen community-based promotive and preventive health services.